THEORY OF PERSONNEL MANAGEMENT PRACTICE: FORMULATION OF THE CONTROL PURPOSE - Azarskov, V. М.; Mashkov, O. A.; Kondratenko, S. P. (Problems of Informatization and Management, 2021)
In the proposed series of scientific articles, the authors from an algorithmic standpoint outline the principles, approaches and methods of personnel management. Existing theoretical approaches are based on heuristic and subjective approaches to the management of complex objects. In the proposed series of scientific articles, the authors consider the procedure of personnel management as a procedure for managing complex objects based on systems analysis. Recently, psychologists have been paying a lot of attention to goal-setting processes, which rightly define the goal as the basis of behavior, which is traditionally a psychological sphere. In [4] the mechanisms of goal setting are considered from these positions, but not related to personnel management processes. In the proposed work, the authors consider the process of formalizing goals in personnel management in the form of presenting them in numerical form.